1996
DOI: 10.1089/mdr.1996.2.163
|View full text |Cite
|
Sign up to set email alerts
|

Penicillin and Beyond: Evolution, Protein Fold, Multimodular Polypeptides, and Multiprotein Complexes

Abstract: As the protein sequence and structure databases expand, the relationships between proteins, the notion of protein superfamily, and the driving forces of evolution are better understood. Key steps of the synthesis of the bacterial cell wall peptidoglycan are revisited in light of these advances. The reactions through which the D-alanyl-D-alanine depeptide is formed, utilized, and hydrolyzed and the sites of action of the glycopeptide and /3-lactam antibiotics illustrate the concept according to which new enzyme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
20
0

Year Published

1997
1997
2001
2001

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 33 publications
1
20
0
Order By: Relevance
“…That the n-PB module of the class B PBP3 is not a transglycosylase is consistent with the fact that it has a different amino acid signature from that of the n-PB module of the bienzymatic (transglycosylase-transpeptidase) PBP1a and PBP1b of class A and of the monofunctional transglycosylases (12,13,28). In addition to its assisted folding function (16), the n-PB module of PBP3 may serve as a "wiring" element connecting the associated acyl serine transferase module to the transglycosylase module of the class A PBP1a and/or PBP1b and to other cell cycle proteins.…”
Section: Discussionsupporting
confidence: 59%
“…That the n-PB module of the class B PBP3 is not a transglycosylase is consistent with the fact that it has a different amino acid signature from that of the n-PB module of the bienzymatic (transglycosylase-transpeptidase) PBP1a and PBP1b of class A and of the monofunctional transglycosylases (12,13,28). In addition to its assisted folding function (16), the n-PB module of PBP3 may serve as a "wiring" element connecting the associated acyl serine transferase module to the transglycosylase module of the class A PBP1a and/or PBP1b and to other cell cycle proteins.…”
Section: Discussionsupporting
confidence: 59%
“…The predicted AmpH protein contains the canonical SXXK, YXN, and KTG activesite motifs of the PBPs and ␤-lactamases (Fig. 4) (15,16). A similarity search using the BEAUTY program (44) indicated that the encoded protein is related most closely to the family of class C ␤-lactamases-15 of the 16 most similar proteins belonged to this group (data not shown).…”
Section: Identification and Subcloning Of Newmentioning
confidence: 98%
“…Each organism contains a complete set of these enzymes, which are all targeted by ␤-lactams. PBPs interact with the antibiotic by forming a relatively stable, covalent complex via the active-site serine (15)(16)(17).…”
mentioning
confidence: 99%